2020
DOI: 10.1038/s41598-020-70888-0
|View full text |Cite
|
Sign up to set email alerts
|

Dietary ceramide 2-aminoethylphosphonate, a marine sphingophosphonolipid, improves skin barrier function in hairless mice

Abstract: Sphingolipids are one of the major components of cell membranes and are ubiquitous in eukaryotic organisms. Ceramide 2-aminoethylphosphonate (CAEP) of marine origin is a unique and abundant sphingophosphonolipid with a C-P bond. Although molluscs such as squids and bivalves, containing CAEP, are consumed globally, the dietary efficacy of CAEP is not understood. We investigated the efficacy of marine sphingophosphonolipids by studying the effect of dietary CAEP on the improvement of the skin barrier function in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…The metabolomic analysis of the present study revealed that several metabolites, such as 2-aminoethylphosphonate, were enriched in the CRA and CRC groups compared with the HC group. 2-Aminoethylphosphonate is a potentially nutritionally active phosphatidyl sphingolipid that significantly increases the content of hydroxy ceramides, which play an important role in the expression of genes related to its biosynthesis-related genes in the skin ( 29 ). Amino acids play an important role in several steps of protein biosynthesis, where they maintain redox homeostasis as both electron donors and acceptors and act as energy sources ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…The metabolomic analysis of the present study revealed that several metabolites, such as 2-aminoethylphosphonate, were enriched in the CRA and CRC groups compared with the HC group. 2-Aminoethylphosphonate is a potentially nutritionally active phosphatidyl sphingolipid that significantly increases the content of hydroxy ceramides, which play an important role in the expression of genes related to its biosynthesis-related genes in the skin ( 29 ). Amino acids play an important role in several steps of protein biosynthesis, where they maintain redox homeostasis as both electron donors and acceptors and act as energy sources ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…No studies have reported the inhibition of cholesterol absorption by CAEP, a sphingolipid possessing a carbon-phosphorus bond, and is often found in bivalves. However, CAEP is hydrolyzed to sphingoid base during the digestive process and can interfere with cholesterol absorption ( 44 ). In this study, SOY-PL contained PtdCho and PtdEtn, and SCO-PL contained PtdCho, PtdEtn, and CAEP.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of these animal studies were conducted using models with disrupted skin caused by ultraviolet (UV) exposure, sodium dodecyl sulfate (SDS) treatment, tape-stripping, and a special commercial diet (HR-AD), a few reports on animals under normal conditions are available (Table ). HR-AD is a magnesium-deficient diet that induces skin damage and atopic dermatitis-like skin symptoms, although the causative mechanism is not clear. , After causing skin perturbation by feeding hairless mice a HR-AD, dietary supplementation of plant-derived glucosylceramide, sphingomyelin, and CAEP can accelerate the recovery of their skin damage, such as increased TEWL and decreased stratum corneum hydration, by changing to a normal diet. In addition, the direct addition of sphingolipids, including plant-derived glucosylceramide and milk-derived sphingomyelin, to the HR-AD diet drastically suppresses skin damage. Exposure to UV radiation is a key factor in the initiation of photoaging and can be characterized by dryness, wrinkling, and mottled pigmentation . Mice with a single-dose UVB-irradiated dorsal skin (20–200 mJ/cm 2 ) were used as the damaged skin model.…”
Section: Skin-improving Effect Of Dietary Sphingolipidsmentioning
confidence: 99%
“…The structure formed by the binding of ω-hydroxyceramides to cornified envelope proteins plays an important role in skin barrier function . In addition, dietary CAEP (from squid) and glucosylceramide (from maize) significantly increased the content of covalently bound ω-hydroxyceramides, and the expression of their biosynthesis-related genes in the skin of HR-AD mice . Considering this evidence, the difference in sphingolipid structures, especially sphingoid bases, is not crucial for the activation of de novo ceramide synthesis in the epidermis.…”
Section: Skin-improving Effect Of Dietary Sphingolipidsmentioning
confidence: 99%